Demand Dispatch Control for Balancing Load with Generation - Ashourpouri, Andisheh (Curtin University, 2018)
There are different methods to implement demand management. In this thesis, a Demand Side Frequency Droop is proposed to calculate the require power reduction. Moreover, Demand Dispatch (DD) can provide ancillary service to the grid and maintains the power system frequency. Besides, to improve the operation of DD, the renewable resources and the storage devices are integrated to the DD. The proposed methods in this thesis have been validated through PSCAD software simulation and MATLAB.